Task-dependent muscle activation during functional upper-Limb tasks in adults with and without chronic non-specific neck pain: A cross-sectional study. - Soylu, Gizem; Ülger, Özlem (Journal of Back & Musculoskeletal Rehabilitation, 2026)
Background: Although many studies explore surface electromyography (sEMG) in static postures, research on muscle activation during dynamic tasks in chronic non-specific neck pain (CNNP) is limited. Objectives: To compare trapezius and sternocleidomastoid (SCM) activation and functional capacity during five upper limb tasks between individuals with CNNP and asymptomatic controls. Methods: This was a cross-sectional comparative observational study. Twenty-seven individuals with CNNP and 25 asymptomatic controls completed five tasks: repetitive reaching (RRT), sustained overhead work (OW), waist-to-overhead lift (OL), fingertip dexterity (FD), and hand–forearm dexterity (HFD). sEMG recorded upper (UT), middle (MT), and lower trapezius (LT), and SCM activity. Functional capacity was assessed using selected WorkWell Systems Functional Capacity Evaluation (WWS-FCE) tasks. Results: CNNP individuals showed greater UT activation across all tasks (p < 0.01, d = 0.78–1.67) and significant MT differences in most conditions (p < 0.01, d = 0.84–1.44). LT showed smaller but significant differences (p < 0.05, d = 0.47–0.84). SCM activity increased during OL (p < 0.01, d = 0.73–1.08) and in one RRT subtask (p = 0.011, d = 0.73). CNNP performed worse than controls in RRT (p < 0.001, d = –1.32 to −1.61), OW (p < 0.001, d = –2.17), OL (p = 0.006–<0.001, d = –0.80 to −1.26), and HFD (p < 0.001, d = –1.06 to −1.36), with no significant FD differences (p > 0.05). Significant Group × Task interactions were observed for UT, MT, and SCM (p < 0.05). Conclusion: Muscle activation profiles in chronic non-specific neck pain change with tasks, highlighting the importance of evaluating functional activities beyond static-posture assessments.